Pengaruh nilai tukar, inflasi dan jumlah uang beredar terhadap indeks harga saham gabungan (IHSG) di bursa efek Indonesia (BEI) tahun 1994-2013 - Yunita Putri Siregar; Rosyetti '; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Capital market in Indonesia is an emerging market which in its development is very vulnerable to macroeconomic condition in general. Macroeconomic condition is one of the factors that affect the performance of the capital market. This study aims to empirically examine the effectof macro variables (exchange rate, inflation and money supply) towardsIHSG (Indonesia Stock Exchange Composite Index) in BEI. This study used a secondary data type. The analytical method used was the method of quantitative analysis using a multiple regression analysis with SPSS version 18.0. The result showed a simultaneous result between the effect of exchange rate, inflation and the number of circulating money supply into IHSG (Composite Stock Price Index)in the period of 1994-2013 with F value was 76.65, sig 0.000, and value of R2 was 0,923which means 92.3% of IHSG in BEI was influenced by exchange rate, inflation and the money supply, while the remaining 7.7% was influenced by other factors that weren’t explained in this studyKeywords : Exchange rate, Inflation, Money Supply, Composite Stock Price Index